Clostridial Spores for Cancer Therapy: Targeting Solid Tumour Microenvironment. (7th June 2012) - Umer, Brittany; Good, David; Anné, Jozef; Duan, Wei; Wei, Ming Q.
Abstract : Solid tumour accounts for 90% of all cancers. The current treatment approach for most solid tumours is surgery, however it is limited to early stage tumours. Other treatment options such as chemotherapy and radiotherapy are non-selective, thus causing damage to both healthy and cancerous tissue. Past research has focused on understanding tumour cells themselves, and conventional wisdom has aimed at targeting these cells directly. Recent research has shifted towards understanding the tumour microenvironment and it's differences from that of healthy cells/tissues in the body and then to exploit these differences for treatmeat of the tumour. One such approach is utilizing anaerobic bacteria. Several strains of bacteria have been shown to selectively colonize in solid tumours, making them valuable tools for selective tumour targeting and destruction. Amongst them, the anaerobic Clostridium has shown great potential in penetration and colonization of the hypoxic and necrotic areas of the tumour microenvironment, causing significant oncolysis as well as enabling the delivery of therapeutics directly to the tumour in situ . Various strategies utilizing Clostridium are currently being investigated, and represent a novel area of emerging cancer therapy. This review provides an update review of tumour microenvironment as well as summary of the progresses and current status of Clostridial spore-based cancer therapies.